Mitochondrial dysfunction induces the invasive phenotype, and cell migration and invasion, through the induction of AKT and AMPK pathways in lung cancer cells - Han, Si-Yoon; Jeong, Yun-Jeong; Choi, Yongsoo; Hwang, Soon-Kyung; Bae, Young-Seuk; Chang, Young-Chae (SPANDIDOS PUBL LTD, 2018)
Mitochondria are well known for their important roles in oxidative phosphorylation, amino acid metabolism, fatty acid oxidation and ion homeostasis. Although the effects of mitochondrial dysfunction on tumorigenesis in various cancer cells have been reported, the correlation between mitochondrial dysfunction and epithelial-to-mesenchymal transition (EMT) in lung cancer development and metastasis has not been well elucidated. In the present study, the effects of mitochondrial dysfunction on EMT and migration in lung cancer cells were investigated using inhibitors of mitochondrial respiration, oligomycin A and antimycin A. Oligomycin A and antimycin A induced distinct mesenchymal-like morphological features in H23, H1793 and A549 lung cancer cells. In addition, they decreased the expression levels of the epithelial marker protein E-cadherin, but increased the expression levels of the mesenchymal marker proteins Vimentin, Snail and Slug. The results of immunofluorescence staining indicated that oligomycin A and antimycin A downregulated cortical E-cadherin expression and upregulated the expression of Vimentin. In addition, oligomycin A and antimycin A increased the migration and invasion of A549 lung cancer cells, and promoted the expression levels of phosphorylated (p)-protein kinase B (AKT) and p-AMP-activated protein kinase (AMPK). Notably, the production of reactive oxygen species by oligomycin A and antimycin A did not affect the expression of EMT protein markers. Conversely, treatment with the AKT inhibitor wortmannin and the AMPK inhibitor Compound C upregulated E-cadherin and downregulated Vimentin expression. These results suggested that oligomycin A and antimycin A may induce migration and invasion of lung cancer cells by inducing EMT via the upregulation of p-AKT and p-AMPK expression.
Keywords: EPITHELIAL-MESENCHYMAL TRANSITION; CARCINOMA CELLS; CADHERIN EXPRESSION; SIGNALING PATHWAY; DOWN-REGULATION; EMT; STRESS; METASTASIS; APOPTOSIS; SNAIL